Nove članice in multikulturnost v Evropski uniji - Dadasović, Miodrag (Organizacija znanja, 2007)
Incorporated inter and multicultural principles in Macedonian legislation represents societyćs basic functioning postulates. Republic of Macedonia tendstoward integration into European Unionćs equal, balanced, ualitative and respectful representation of different cultures and different cultural identities. Centers of cultures, libraries, reading rooms and corners of many Balkan and other Europećs states, represent, affirm and bring closer differentcultures toward integration into European Unionćs unique cultural society.
Keywords: culture; European Union; Evropska unija; kultura; kulturna identiteta; Makedonija; Republic of Macedonia